Psychometric properties of the Taiwan version of Emotion Dysregulation Inventory in Autism Spectrum Disorder - Chen-Yu Kuo; Chun-Hao Liu; Yu-Chen Huang; Sophie Hsin-Yi Liang; Hsiang-Yuan Lin; Hsing-Chang Ni (Journal of the Formosan Medical Association)
Background: While the Emotion Dysregulation Inventory (EDI) for autistic people has been validated in many Western countries, its psychometric properties have remained unclear in East Asia. Methods: We translated the EDI into traditional Chinese and evaluated its psychometric properties among autistic children and youth in Taiwan. We enrolled 200 participants (182 male/18 female) aged 7–30 years from five clinical trials and conducted secondary analyses, assessing internal consistency reliability, confirmatory factor analysis, and convergent validity. Results: Our results showed that the Taiwan version of the EDI had strong internal consistency (Cronbach's alpha are 0.978 and 0.864 for each factor). Confirmatory factor analysis demonstrated acceptable fit of two-factors structure. The Taiwan version of EDI showed good convergent validity with established measurements including the Aberrant Behavior Checklist-Irritability subscale and Child Behavior Checklist-Dysregulation Profile. Conclusion: Our findings support the Taiwan version of EDI is a reliable and potentially valid instrument for assessing emotion dysregulation in autistic children and youth in Taiwan.